Hemodynamical Flows: Modeling, Analysis and Simulation (Oberwolfach Seminars) - Galdi, Giovanni P. (Springer, 2017)
This book surveys research results on the physical and mathematical modeling, as well as the numerical simulation of complex fluid and structural mechanical processes occurring in the human blood circulation system. Topics treated include continuum mechanical description; choice of suitable liquid and wall models; mathematical analysis of coupled models; numerical methods for flow simulation; parameter identification and model calibration; fluid-solid interaction; mathematical analysis of piping systems; particle transport in channels and pipes; artificial boundary conditions, and many more.